Bactericidal, quorum quenching and anti-biofilm nanofactories: a new niche for nanotechnologists. (19th May 2017) - Singh, Brahma N.; Prateeksha,; Upreti, Dalip K.; Singh, Braj Raj; Defoirdt, Tom; Gupta, Vijai K.; De Souza, Ana Olivia; Singh, Harikesh Bahadur; Barreira, João C. M.; Ferreira, Isabel C. F. R.; Vahabi, Khabat
Abstract: Despite several conventional potent antibacterial therapies, bacterial infections pose a significant threat to human health because they are emerging as the leading cause of death worldwide. Due to the development of antibiotic resistance in bacteria, there is a pressing demand to discover novel approaches for developing more effective therapies to treat multidrug-resistant bacterial strains and biofilm-associated infections. Therefore, attention has been especially devoted to a new and emerging branch of science "nanotechnology" to design non-conventional antimicrobial chemotherapies. A range of nanomaterials and nano-sized carriers for conventional antimicrobial agents have fully justified their potential to combat bacterial diseases by reducing cell viability, by attenuating quorum sensing, and by inhibiting/or eradicating biofilms. This communication summarizes emerging nano-antimicrobial therapies in treating bacterial infections, particularly using antibacterial, quorum quenching, and anti-biofilm nanomaterials as new approaches to tackle the current challenges in combating infectious diseases.